2012
DOI: 10.1007/s00468-012-0742-3
|View full text |Cite
|
Sign up to set email alerts
|

Testing the packing rule across the twig–petiole interface of temperate woody species

Abstract: Theories that incorporate the area-preserving rule of Leonardo da Vinci predict that the sum of the crosssectional lumen area of xylem conduits (vessels or tracheids) is constant across different levels of branching. If true, this rule obtains the packing rule, according to which (1) vessel cross-sectional lumen area (A) will negatively and isometrically scale to vessel number per unit area (N) and (2) the distal to proximal vessel diameter ratio (DR = D n?1 /D n ) should scale as the -1/2 power of the distal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…However, despite the increasing return on hydraulic performance enabled by the variation in Dmh, there must be a trade-off between Dmh and fvessel. This statement is in agreement with the theoretical model of the packing rule (Sperry et al 2008, Chen et al 2012), which predicts that fvessel should isometrically scale with conduit size and thus allows for the area-preserving branching of vessels across different branching levels.…”
Section: Discussionsupporting
confidence: 90%
“…However, despite the increasing return on hydraulic performance enabled by the variation in Dmh, there must be a trade-off between Dmh and fvessel. This statement is in agreement with the theoretical model of the packing rule (Sperry et al 2008, Chen et al 2012), which predicts that fvessel should isometrically scale with conduit size and thus allows for the area-preserving branching of vessels across different branching levels.…”
Section: Discussionsupporting
confidence: 90%
“…As in the case of tapering rules, the area-preserving rule has been tested with regard to cross-sectional areas of ring increments, SW and whole axes excluding bark (Nikinmaa, 1992;Yamamoto and Kobayashi, 1993;Hatsch, 1997;Sone et al, 2005Sone et al, , 2009. Furthermore, it should be noted that Leonardo da Vinci's rule was also tested at a microanatomical scale by considering xylem conduit dimensions and comparing it with the Murray law to investigate how branching systems optimize hydraulic flux to woody and leafy organs (McCulloh et al, 2003;Chen et al, 2012;Price et al, 2014;Carvalho et al, 2017a, b).…”
Section: Relation With Leonardo Da Vinci's Rule (Area-preserving Rule)mentioning
confidence: 99%
“…This finding also suggests that because Sperry's packing rule optimizes the balance between conduit number and size after mechanical requirements have been met, xylem in petioles is likely to be functioning mechanically to some extent, but xylem alone is unable to meet the mechanical requirements of the petiole. Shrubs and trees appear to be mixed in their adherence to the packing rule in larger studies at the stem-leaf junction (Chen et al, 2012). We propose that this wide variation in adherence results from the combination of different proportions of tissues for petiole support in conjunction with anatomical variation in bundle number, as well as remarkable plasticity in petiole construction.…”
Section: Discussionmentioning
confidence: 83%
“…Values range from -1.44 in oaks to -2.73 in maples (Savage et al, 2010;Savage et al, 2015). A previous study found limited evidence for adherence to the packing rule across the twig-petiole interface (Chen et al, 2012), but vessel packing in petioles has not been further investigated. Vessel packing in petioles could differ from that in woody stems because xylem in petioles is commonly primary xylem.…”
mentioning
confidence: 94%